Period/frequency estimation of a nonlinear oscillator. Issue 3 (December 2019) - Tian, Dan; Liu, Zhi
Fast estimation of a nonlinear oscillator is very much needed in engineering, the perturbation method is valid only for weakly nonlinear oscillators. This paper gives some simple formula for this purpose, only simple calculation is needed to have a relatively high accuracy of the estimated frequency.